Analisis Peran dan Strategi Pengembangan Koperasi di Bengkulu - Wardana, Mohamad Irfan Surya; Ismail, Ismail; Mursalin, Imam Abdurrahman; Rosyadi, Akhmad Alfian (SENTRI: Jurnal Riset Ilmiah, 2025)
This study analyzes the role and development strategies of cooperatives in Bengkulu Province by identifying both internal and external challenges and formulating strengthening strategies based on SWOT analysis and the Eisenhower Matrix. According to Law Number 25 of 1992, cooperatives are recognized as a pillar of the national economy, playing a strategic role in improving member welfare and promoting regional economic growth. However, the development of cooperatives in Bengkulu still faces significant obstacles, including low digital and financial literacy among members, weak governance practices, limited capital, and adaptation challenges in the digital era amidst competition from modern retail and e-commerce platforms. The analysis shows that cooperative development efforts require enhanced multi-stakeholder collaboration, digital transformation, capacity building for cooperative managers, and regulatory adjustments, including the acceleration of village/urban cooperatives (Koperasi Desa/Kelurahan Merah Putih) as mandated by Presidential Instruction Number 9 of 2025. The strategic recommendations include improving transparency and accountability, strengthening strategic partnerships, modernizing cooperative services, and optimizing the roles of central and regional governments in supporting capacity building and financing. These findings are expected to serve as inputs for formulating adaptive, inclusive, and sustainable cooperative development policies at the regional level.